The Impact of Prepare-Enrich Program based on Distance Learning on Marital Satisfaction among Newly-wed Couples: The role of Demographic Factors - Ghiasi, Nasrin (International Journal of Psychosocial Rehabilitation, 2020)
Modern methods have less been considered in couples’ learning and their needs in practice. Thus, the present study aimed at determining the impact of marriage enrichment through distance learning in marital satisfaction of newly-wed couples with an emphasis on the role of demographic factors. The present study is experimental. The population were selected based on the inclusion and exclusion criteria through simple random sampling (N=80couple) and were placed randomly into experimental (N=40couple) and control (N=40couple) group. The intervention was conducted as distance for 12 weeks. The data were collected by Enrich couple scale and demographic information questionnaire. Data analysis was performed by descriptive statistics, Independent t-test, ANCOVA, and MANCOVA. The results showed a significant difference between the two groups in terms of marital satisfaction after intervention (P